Funcionarios de la Unidad de Aseo. (UNED, 2024)
Aparecen de pie, a la izquierda Orlando Alvarado Valverde, Luis Gustavo Meléndez Salas, Carlos Montoya Rodríguez, Carlos Valverde Murillo, Alejandro Rojas Sanabria, Álvaro Montero Villalta, Rafael Ángel Artavia Arguedas, en el mismo orden, Kattya Torres Chinchilla, Blanca Estela Romero Iraheta, Marta Jarquín Ramírez, Cecilia Rodríguez Fernández, Karol Fallas Méndez, Lisbeth Chacón Wille, Jenny Céspedes Picado